Successful Counselors' Perceptions of the Performance Dimensions of Therapeutic Competence: A Qualitative Research - Morteza Karami; Mousa Choupani (Kerman University of Medical Sciences, 2020)
Introduction: Community development and its prompting problems made it known that we are significantly in need of mental health specialists, especially counselors. The aim of the present study was to probe the quality of successful counselors' perceptions of the performance dimensions of therapeutic competence. Methods: This study was conducted using the phenomenological approach. The purposive sampling method was adopted to choose 20 counselors (interviewees) to participate in the study from amongcounselors at Shamim Counseling Centers of Islamic Revolutionary Guard Corps in 2016.All the interviews were tape-recorded and then transcribed line by line. Finally, they were analyzed in accordance with interpretation analysis method. Results: In this paper, 20 semi-structured interviews were conducted. The analyzed data of the interviews led to the identification of 8 main themes (Theoretical proficiency, Interdisciplinary knowledge, Insight into context, Specialization in intervention levels, Clinical specialization, Multicultural competence, Focusing on common therapeutic factors and Holism) and 30 sub-themes in terms of performance dimensions of therapeutic competence. Conclusion: The results of this study can help develop counselors' educational programs and evaluate counselors' level of competence and self-efficiency in the recruitment centers.